PENGARUH DIGITAL MARKETING, PRODUK WISATA, DAN WORD OF MOUTH TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN (Studi Pada Pengunjung Wisata Pantai Klayar di Kabupaten Pacitan) - Janatin Naimah (Jurnal Ilmiah Mahasiswa FEB, 2016)
The role of digital marketing is one of the appropriate marketing strategies for the tourism sector. The use digital marketing for tourism should be with tourism products that can attract consumers to visit. Visitors who are satisfied with tourism products will transact others. The purpose of this study was to analyzing the influence of digital marketing, tourism product and word of mouth on the tourist visit decision in Klayar Beach. The research uses 130 samples using non probability sampling method with purposive sampling technique. Data analysis method used was multiple linear regression with SPSS 21.0 for Windows. The result of this study show that digital marketing variable has significant influence on the tourist visit decision with a significance of 0,000. Tourist product variable also have significant  influence on the tourist visit decision with a significance of 0,000. Word of mouth variable has significant influence also to the tourist visit decision with significance value equal to 0,045.Keywords: Digital Marketing, Tourism Product, Word of Mouth and Visit Decision.